Victim-Offender Overlap Among Incarcerated Youth in the United States: A Bivariate Probit Analysis Using National Data - Lo, Tzu-Ying (Victims & offenders, 2025)
For many crimes, people who are the perpetrators may also be the victims. While several studies have investigated the victim-offender overlap, very few have examined the relationship for incarcerated youth where institutional conditions can exacerbate the overlap. Drawing on ideas from routine activities theory, this study explores the victim-offender overlap among incarcerated American youth using data from the 2008–2009 National Survey of Youth in Custody (NSYC-1, N = 8,625) and the 2012 National Survey of Youth in Custody (NSYC-2, N = 8,125). Findings from a bivariate probit regression indicate that younger age, higher facility populations, negative perceptions of officer legitimacy, experiences of filing complaints against staff, in-facility gang membership, and longer durations of time served in the facility increase the risk of both offending and victimization. The study illustrates the applicability of routine activity theory in understanding the victim-offender overlap in juvenile correctional settings and provides implications for policy and intervention strategies.